Application of Composite Coagulant In Removing Heavy Metals from Leachate via Coagulation-Flocculation Process - Gustiabani, Zures; Mohd Zin, Nur Shaylinda; Mohd Salleh, Siti Nor Aishah; Gopalakrisnan, Yashni (Penerbit UTHM, 2020)
Leachate contains various particles which could contaminate ground water. Proper leachate control method must be selected for good water quality. One of them is by using coagulation-flocculation with improved material as composite coagulant (CC). This chapter aims to evaluate optimum CCs’ ratio and dosage, and leachates’ pH by CC made from tapioca peel powder (TPP) and polyaluminium chloride (PAC) through the heavy metals reduction in copper (Cu), zinc (Zn), and chromium (Cr) from Simpang Renggam landfill. Tapioca peel from industry was cleaned and mixed with distilled water, filtered, and left under the sun to dry up. By doing jar test of ten ratios of CC and eight dosages, optimum ratio and dosage of CC by heavy metals reduction was determined. The initial and final heavy metal concentrations were measured by ICP-MS. The highest percentage removal (2:9, 3500 mg/L) in terms of Cu, Zn, and Cr was 51.14, 79.63, and 79.23, respectively. Compared to the ratio 1:10, at optimum conditions (4000 mg/L), was 40.51, 83.43, and 91.16 removals, respectively. Ratio 2:9 was chosen because contained more TPP that could save cost and reduce the use of chemical coagulant. It could be determined that the optimum ratio and dosage of CC was 2:9, 3500mg/L, and the optimum sample pH 6 with removals of Cu, Zn, Cr was 55.30, 29.80, 74.98, respectively.